2004
DOI: 10.1002/art.20666
|View full text |Cite
|
Sign up to set email alerts
|

Early response to immunosuppressive therapy predicts good renal outcome in lupus nephritis: Lessons from long‐term followup of patients in the Euro‐Lupus Nephritis Trial

Abstract: Objective. In the Euro-Lupus Nephritis Trial (ELNT), 90 patients with lupus nephritis were randomly assigned to a high-dose intravenous cyclophosphamide (IV CYC) regimen (6 monthly pulses and 2 quarterly pulses with escalating doses) or a low-dose IV CYC regimen (6 pulses of 500 mg given at intervals of 2 weeks), each of which was followed by azathioprine (AZA). After a median followup of 41 months, a difference in efficacy between the 2 regimens was not observed. The present analysis was undertaken to extend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
192
2
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(214 citation statements)
references
References 15 publications
13
192
2
7
Order By: Relevance
“…The influence of renal reserve at baseline and after treatment on long-term renal outcome has been reported previously (11,12). These data thus highlight the complementary merits of assessing overall renal function and performing histologic examination of a fraction of renal parenchyma.…”
supporting
confidence: 59%
“…The influence of renal reserve at baseline and after treatment on long-term renal outcome has been reported previously (11,12). These data thus highlight the complementary merits of assessing overall renal function and performing histologic examination of a fraction of renal parenchyma.…”
supporting
confidence: 59%
“…Many studies have come to the conclusion that the effect of the low-dose therapy is comparable with the recommended high-dose regimen and with a considerably low incidence of infections [3,[11][12][13]. However, our results showed that the incidence of infections between the two groups had no notable differences.…”
Section: Discussioncontrasting
confidence: 57%
“…These include increased disease recognition with more sensitive diagnostic tests, earlier diagnosis and treatment [18,19].…”
Section: Discussionmentioning
confidence: 99%